後方散乱電子回折（EBSD）によるグリーンランドNEEMアイスコアの結晶組織解析 - 繁山, 航; 永塚, 尚子; 本間, 智之; 高, 田守昌; 東, 久美子; Ilka, Weikusat; Martyn, R. Drury; Ernst-Jan, N. Kuiper; Gill, M. Pennock; Ramona, V. Mateiu; 東, 信彦; Dorthe, Dahl-Jensen; et al. (2017)
第8回極域科学シンポジウム/特別セッション：[S] 先端的技術で切り開く極域科学 －極域観測における計測、分析、解析の最前線－ 12月8日（金）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Special session: [S] Polar science developed by leading-edge technology - on the frontiers of measurement and analysis in polar science - Fri. 8 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object